Cleaner Hearths, Better Homes : New Stoves for India and the Developing World - Barnes, Douglas F.; Kumar, Priti; Openshaw, Keith (New Delhi: Oxford University Press and World Bank, 2012)
For people in developed countries, burning fuel wood in an open hearth evokes nostalgia and romance. But in developing countries, the harsh reality is that several billion people, mainly women and children, face long hours collecting fuel wood, which is burned inefficiently in traditional biomass stoves. The smoke emitted into their homes exposes them to pollution levels 10-20 times higher than the maximum standards considered safe in developed countries. And the problem is not out of the ordinary. The majority of people in developing countries at present cannot afford the transition to modern fuels. Today, close to one half of the world's people still depend on biomass energy to meet their cooking and heating needs. This book should be of interest to policymakers and scientists across a broad spectrum of disciplines from health, environment, and economics to sociology, anthropology, and physics. Indeed, the hands of many specialists are required to ensure successful stove programs, which call for social marketing, stove engineering, development of standards, promotion of private and commercial enterprises, and appropriate subsidy schemes. That the book's authors represent diverse disciplines sociology, physics, and forest economics underscores the range of perspectives needed to tackle the issues involved in the commercial promotion of improved stoves. The impetus for writing this book started at the end of a World Bank project on the health implications of indoor air pollution, which coincided with the Government of India's (GoI) cancellation of its 20-year program on improved stoves. The government's decision came as no surprise, given the program's mixed results.